The Cyphomyrus Myers 1960 (Osteoglossiformes: Mormyridae) of the Lufira basin (Upper Lualaba: DR Congo): A generic reassignment and the description of a new species. Issue 5 (18th February 2020) - Mukweze Mulelenu, Christian; Katemo Manda, Bauchet; Decru, Eva; Chocha Manda, Auguste; Vreven, Emmanuel
Abstract: Within a comparative morphological framework, Hippopotamyrus aelsbroecki, only known from the holotype originating from Lubumbashi, most probably the Lubumbashi River, a left bank subaffluent of the Luapula River, is reallocated to the genus Cyphomyrus . This transfer is motivated by the fact that H. aelsbroecki possesses a rounded or vaulted predorsal profile, an insertion of the dorsal fin far anterior to the level of the insertion of the anal fin, and a compact, laterally compressed and deep body. In addition, a new species of Cyphomyrus is described from the Lufira basin, Cyphomyrus lufirae . Cyphomyrus lufirae was collected in large parts of the Middle Lufira, upstream of the Kyubo Falls and just downstream of these falls in the lower Lufira and its nearby left bank affluent, the Luvilombo River. The new species is distinguished from all its congeners, that is, firstly, from C. aelsbroecki, C. cubangoensis and C. discorhynchus, by a low number of dorsal fin rays, 27‐32 ( vs. higher, 36 (37), 34 (33‐41) an 38 (38‐40), respectively) and, secondly, from C. aelsbroecki, C. cubangoensis, and C. discorhynchus by a large prepelvic distance, 41.0–43.8% L S ( vs. shorter, 39.7%, 38.9–39.1% and 37.0–41.0% L S, respectively). The description of yet another new species for the Upemba National Park and the Kundelungu National Park further highlights their importance for fish protection and conservation in the area. Hence, there is an urgent need for the full integration of fish into the management plans of these parks.